The Interface of English Language Teaching and Remote Educational Technology - Nurbianta Nurbianta; Mark Philip C Paderan; Zohri Hamdani (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2020)
Adapting to the “New Normal” is the prime issue that educational institutions are facing nowadays, thus, adjustments in teaching and learning has to be done to reach all students despite the limitations in the face to face interaction. This paper has been initiated to share the voices of the teachers and students’ circumstances and struggles in the transition due to COVID-19 pandemic. Through this paper, the perception on the psychological, and pedagogical concerns shall be given overview and the interface of English Language Teaching and Remote Educational Technology shall be given light to provide beneficial concept for both teachers and students This shall pave way for the continuous support and development in educational institutions and fronliners